Sistem Cash on Delivery Dalam Prespektif Hukum Perlindungan Konsumen dan Ekonomi Islam - Dewi, Marchelia Fitria; Prayuti, Yuyut (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
Economic activities are closely related to transactions such as to support the needs of oneself, family, and the wider community. In connection with that, buying and selling through electronic media such as using the Cash On Delivery payment system which is a form of trade or business interaction is one of the economic phenomena of mu'amalah that is currently rife. Therefore, Islam has taught that the terms and conditions of buying and selling transactions must be in accordance with the Shari'a, such as avoiding defects such as not fulfilling the conditions of the goods being traded, both the type, quality, and quantity, price, and there is no element of coercion, fraud, harm, or other conditions that make up the pillars of buying and selling. So the purpose of this research is to examine the legal protection of cash on delivery transactions in online buying and selling from the perspective of consumer protection and Sharia economic law. This research is a descriptive analytical normative legal research, using legislative and conceptual approaches. As a result, buying and selling is a fundamental component of Islamic Shariah, and adhering to these pillars is essential for a successful and legitimate transaction.Accordingly, Islamic jurisprudence deals with the order of purchase and sale, where the permissibility of transactions with al-salam aims to increase the convenience of business by allowing goods to be delivered later.Thus the use of the COD method, which allows payment on the spot, reduces fakes and hazards such as goods that do not match the size, shape, color, or packaging ordered.